Current status and proposed roles for nitric oxide as a key mediator of the effects of extracellular nucleotides on plant growth - Salmi, Mari L.; Clark, Greg; Roux, Stanley J. (Frontiers in Plant Science, 2013)
Recent data indicate that nucleotides are released into the extracellular matrix (ECM) during plant cell growth, and that these extracellular nucleotides induce signaling changes that can, in a dose-dependent manner, increase or decrease the cell growth. After activation of a presumed receptor, the earliest signaling change induced by extracellular nucleotides is an increase in the concentration of cytosolic Ca2+, but rapidly following this change is an increase in the cellular level of nitric oxide (NO). In Arabidopsis, mutants deficient in nitrate reductase activity (nia1nia2) have drastically reduced nitric oxide production and cannot transduce the effects of applied nucleotides into growth changes. Both increased levels of extracellular nucleotides and increased NO production inhibit auxin transport and inhibit growth, and these effects are potentially due to disruption of the localization and/or function of auxin transport facilitators. However, because NO- and auxin-induced signaling pathways can intersect at multiple points, there may be diverse ways by which the induction of NO by eATP could modulate auxin signaling and thus influence growth. This review will discuss these optional mechanisms and suggest possible regulatory routes based on current experimental data and predictive computational analyses.